Development and evaluation of organic biofertilizer using oil palm empty fruit bunch as composted medium for vegetable gardening - Eza Azuren, Yusuf (Universiti Malaysia Sarawak, (UNIMAS), 2014)
In Malaysia, the oil palm industries generate approximately 90 million tonnes of renewable biomass each year. The l;;mpty fruit bunch (EFB) contributes the highest amount of solid waste from this industry. Various studies were conducted on managing the solid waste such as EFB by means of composting process. The objectives of this study were to develop organic biofertilizer using the oil palm empty fruit bunch as medium using effective microbes and to test and evaluate the use of biofertilizer developed on the vegetable gardening. The study revealed that vegetable of Capsicum annuum L. (Chili) that grew with the mature compost that were spIked with Burkholderia unamae PI 0 (Bioctiv-SFI) and Enlerobacter cloacae PII (Bioactiv-SF2) revealed to have positive impacts on the growth of the Chilies. The treatment with the mature compost cured with Enterobacter cloacae (P II) showed the best result among the other treatments. This included the highest values of height, greater growth of roots formation, and early induction of flowering. Further study should be conducted in longer period and bigger sample size in order to get more data on the application of these two types ofbacterial on the vegetable garden.